Steakhouse / Muhammad Syahmi Mohd Yusoff ...[et al.] - Mohd Yusoff, Muhammad Syahmi; Mohd Azlan, Muhammad Rais; Abdul Yazid, Nurul Umairah; Zul-Kharnain, Siti Nursyazweena (2024)
Tender Bite is a steakhouse restaurant that stands as a culinary haven where the art of steak meets an immersive dining experience. Tender Bite steakhouse located at Jalan Horizon Perdana 5, Horizon Hills, Iskandar Puteri, Johor Bahru. Tender Bite steakhouse was led by 4 partners which are general manager, administration manager, marketing manager and financial manager. Everyone plays their roles so that Tender Bite can improve to become the best steakhouse in the city. At Tender Bite, we source only the finest cuts of beef, lamb, and Wagyu, ensuring a dining experience defined by tenderness, succulence, and rich flavor profiles. Our commitment to quality is reflected in every bite. There are also beverages to be served like carbonated soft drinks; Coca-cola, Mountain Dew and Sprite. For those who don't like to drink carbonated drinks, we also served another drink like passion fruit, for example Heaven and Earth. The Tender Bite target market are students, foreigners and western food lovers. That’s why our steakhouse is located near the city and housing, this is a strategic place where all our target markets come by